The Role of Imported Intermediate Inputs in the Indonesian Economy - Rahardja, Sjamsu (World Bank, Jakarta, 2015)
The recent emergence of a persistent deficit in Indonesia s trade balance has triggered concerns over reliance on imports. Notably, imports of intermediate inputs and capital goods have been on the rise over the last decade. Apart from firms partaking in the emergence of global production networks, firms imported intermediates for various reasons, including value, variety, and quality. Concerns may arise about the impact that an increase in reliance on imported inputs may have on domestic jobs, and value added. A careful examination of sector and firm level data from the Indonesian manufacturing sector reveals that: (1) the growth of intermediates imports roughly matches the growth of Indonesian GDP, implying a relatively stable reliance on imported inputs. (2) Users of imported inputs in Indonesia are exceptional performers: they grow faster in terms of output, value added and employment, they are more productive, and they pay higher wages. (3) The increased availability of imported inputs has contributed to improved product quality in Indonesian manufacturing. Larger shares of imported inputs in total inputs, as well as lower tariffs on inputs, are associated with a higher probability of producing high quality goods. (4) Firms product diversification processes have been boosted by lower tariffs on inputs, and by increased usage of imported versions. In light of these results, this note argues that facilitating the import of intermediate products can help the Indonesian economy to diversify, avoid being stuck in low-skilled processing or around natural resource based manufacturing, and to climb up the value chain. Such an approach, however, is not sufficient in isolation and active policies are needed to increase firms absorptive capacities and workers skills.